FEATURES OF INNOVATIVE PROJECT MANAGEMENT AT THE ENTERPRISE - Koliedina , K.O.; Hrechanyk , N.Yu. (The actual problems of regional economy development, 2025)
Modern business conditions, characterized by the dynamic changes of the external environment, the rapid pace of scientific and technological progress, and the constant shortening of the life cycle of goods and services, compel enterprises to systematically search for sources to improve their operational efficiency. It has been established that achieving the set goals is possible if the enterprise chooses an innovative development path as a key factor in gaining sustainable competitive advantages. It is substantiated that the implementation of innovative development within an enterprise is achieved through the introduction of a set of effective, diverse, and multifaceted innovation projects. At the same time, it is appropriate to define the effectiveness of an enterprise’s innovative development through the effectiveness of the totality of its innovation projects. It is noted that the justification of the effectiveness of an innovation project should be based on functional aspects such as technical, commercial, institutional, social, environmental, financial, and economic factors. The necessity of applying project analysis methodology in the management of an enterprise’s innovation projects is proven. This methodology makes it possible to solve a number of urgent issues, namely: to foresee all consequences of innovation project implementation, which may be either positive or negative; to determine the external and internal conditions for implementing project decisions by establishing their qualitative and quantitative characteristics; to minimize the risks of errors during the preparation and implementation of the enterprise’s innovation projects; and to ensure the successful functioning of planned projects through project risk management. The types of break-even points for innovation projects are systematized, distinguishing between the accounting break-even point (which covers accounting costs, including constant costs with depreciation charges), the cash break-even point (which covers only constant costs), and the financial break-even point (which allows to recover the amount invested into the project at zero profitability in future). A method for calculating the financial break-even point of an enterprise’s innovation projects is proposed, particularly under conditions of producing several types of products or the asynchronous implementation of projects during the innovation development process. This method establishes the critical production volume capable of covering not only current expenses but also the amount of investments through annuity payments. The practical value of the research lies in the possibility of applying the proposed methodology for evaluating the effectiveness of innovative projects in the practical activities of Ukrainian enterprises.